Combatting Social Exclusion: "Safe Space" and the Dynamics of Inclusion at a Homeless Farming Site. Issue 2 (4th March 2017) - Bullock, Heather E.; Truong, Shirley V.; Chhun, Lina
ABSTRACT: This study assessed how discrimination and antihomeless ordinances contribute to exclusion, and the meanings and functions of "safe space" among 25 women and men associated with a farming training site who were currently or formerly unhoused. Respondents reported widespread exclusion and interpersonal and institutional discrimination, with the farm identified as a "safe space" from the pervasive stigmatization and surveillance that characterized interactions in the broader community. However, in constructing the farm as a "safe space, " some respondents distanced themselves from unhoused people who were unaffiliated with the farm. Implications for reducing exclusion and fostering "safe spaces" among people experiencing homelessness are discussed.